(untitled) (Journal of Engineering and Health Sciences, 2023)
The anxiety of university students has become increasingly vital since online learning has become the first platform for delivering education as the COVID-19 crisis has interrupted the common learning process of students. A cross-sectional study was conducted on 409 participants. A self-administered questionnaire was given to the participants that fit the inclusion criteria via online platform. The general objective of this study is to assess the anxiety on online learning during the pandemic COVID-19 among undergraduate students at the School of Health Sciences, USM, Kelantan. The data was analyzed by descriptive statistics and Chi-Square test by using Statistical Package of Social Sciences (SPSS) 26.0. Most of the participants have a normal range of anxiety 347 (84.8%) with only 53 (13.0%) experienced mild to moderate anxiety levels and only nine (2.2%) experienced marked to severe anxiety levels. There is no statistically significant association between socio-demographic data (gender, age, ethnicity, field of study, year of field, current accommodation) and level of anxiety on online learning. Proper interventions for those experienced anxiety while conducting online learning during pandemic so that the undergraduate students can have good quality of academic performance as well as good mental health.